English drama at the German theatre in Ljubljana in the last decades of the Habsburg monarchy - Rubik, Margarete (Acta neophilologica, 2012)
This article examines the English repertoire of the German theatre in Ljubljana in the last decades of the Habsburg monarchy and its reception by the local German newspaper, Laibacher Zeitung. It considers only drama, not operas or operettas. The English plays were, of course, performed in translation, in German, as opposed to the plays performed in the Slovenian language from the late 18th century on and especially within the Dramatično društvo circle established in 1867. The choice of performances gives interesting insights into the late 19th century attitude towards English culture as well as the self-image fostered by the German stage in Ljubljana.
Keywords: angleška dramatika; English drama; English theatre; German theatre; nemško gledališče